(untitled) (Materiali di Estetica. Terza serie, 2018)
In the lecture for students entitled Contributi della filosofia alla psicoanalisi (2010) Alfredo Civita dealt with Paul Ricoeur, philosopher and author in 1965 of Dell’interpretazione. Saggio su Freud. Ricoeur’s research is framed in a critique not of a scientific but of a humanistic nature. Ricoeur’s reading is a hermeneutical reading. The materials on which psychoanalysis works – dreams, free associations and so on – are and could nothing else than be texts. So they present themselves as narratives.